Evaluation of Antibiotic Use in Kazakhstan for the Period 2017-2019 Based on WHO Access, Watch and Reserve Classification (AWaRe 2019) - Gulzira Zhussupova; Dinara Utepova; Galiya Orazova; Saule Zhaldybayeva; Galina Skvirskaya; Kanat Tossekbayev (MDPI AG, 2021)
The purpose of this study is to conduct a comparative analysis of the consumption of antibiotics for systemic use reimbursed by the state in Kazakhstan for 2017-2019 with the Access, Watch, and Reserve classification (AWaRe 2019) of the World Health Organization (WHO). The evaluation of the consumption of antibiotics for systemic use in Kazakhstan for 2017-2019 was carried out using the ATC/DDD methodology in accordance with the WHO AWaRe classification. The study used data on all antibiotics that were centrally purchased by a single purchaser during the study period. To understand how often Access group antibiotics are taken in Kazakhstan, the top-10 most consumed antibiotics were additionally studied. The results of a comparative analysis of the antibiotics for systemic use consumption for 2017-2019 by the Access, Watch, and Reserve groups showed a negative trend of a decrease in the consumption of Access group drugs from 1.17 defined daily dose (DDDs) per 1000 inhabitants per day (DID) (39%) in 2017 to 0.59 DID (30%) in 2019. There is an increase in consumption of Watch group antibiotics from 1.84 DID (61%) in 2017 to 1.37 DID (68%) in 2019, as well as an increase in consumption of Reserve antibiotics from 0.001 DID (0.03%) to 0.4 DID (2.11%). In recent years in Kazakhstan, there has been a decrease in the consumption of Access group antibiotics. In addition, the Watch group antibiotics are widely consumed with a certain upward trend. In 2019, one Reserve antibiotic was included in the top-10 most commonly consumed antibiotics. There is a predominant consumption of parenteral forms of antibiotics for systemic use in the country.